2020
DOI: 10.3390/jcm9051376
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Extracorporeal Shock Wave Therapy on Hypertrophic Scars of the Hand Caused by Burn Injury: A Prospective, Randomized, Double-Blinded Study

Abstract: Postburn hypertrophic scarring is a common complication in burn injuries to the hands, often associated with impaired hand function. We evaluated the effects of extracorporeal shock wave therapy (ESWT), compared to a sham stimulation therapy, on hypertrophic scars of the hand caused by burn injury and investigated its effects on hand function. This was a double-blinded, randomized, controlled trial of 48 patients with a burn to their dominant right hand. The parameters of ESWT were as follows: energy flux dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“… 2 3 4 5 6 We transformed the effects of ESWT on hypertrophic scars into the clinical results as POSAS scores, and most of the POSAS subscales were significantly improved after treatment. Apart from the previous studies, which included only the hypertrophic scars following burn wounds, 4 8 15 the current study also included the various etiologies of hypertrophic scars to extend the indications of using ESWT in other causes of hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 3 4 5 6 We transformed the effects of ESWT on hypertrophic scars into the clinical results as POSAS scores, and most of the POSAS subscales were significantly improved after treatment. Apart from the previous studies, which included only the hypertrophic scars following burn wounds, 4 8 15 the current study also included the various etiologies of hypertrophic scars to extend the indications of using ESWT in other causes of hypertrophic scars.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of applications highlights the versatile benefits and regenerative potential of ESWT. 4 5 6 7 8 9 10 11 ESWT transmits a mechanical force via an acoustic wave to facilitate wound healing. The force stimulates the release of neuropeptides from nerve endings and improves wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two years, a high number of publications on the effects of SWT on burn scars was presented. A double-blinded, randomized, controlled trial of 48 patients with a burn to their dominant right hand revealed beneficial effects on pain, scar thickness, vascularity, and hand function [85]. Another study compared the efficacy of Triamcinolon Acetonide injections (TAI) alone, or in combination with SWT, to treat keloids.…”
Section: Shockwave Therapymentioning
confidence: 99%
“…20,[30][31][32] To summarise, there were nine RCT studies involving 422 patients included in our systematic review and meta-analyses. 20,25,[28][29][30][31][32]34,35 The major subject characteristics of the nine selected articles are outlined in Table 1. All these studies were published within the last 5 years (from 2016 to 2021).…”
Section: T a B L E 1 Study Design And Patient Characteristics Of Incl...mentioning
confidence: 99%